European Gender Structures in a Global Perspective - Wiesner-Hanks, Merry (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
For many historians, this conference is already extremely large in its scope—ranging over five centuries and across all of Europe, which in the case of the conference actually means all of Europe and not just England, France and Italy. I would like in these opening remarks to do something even broader: to place issues involving gender, power, and authority in Europe during these centuries, especially those issues that set out categories of less favored and more favored, within a global context.